Analisa dan Perancangan Aplikasi Kearsipan (E-Arsip) Menggunakan UML - Irkham, Ahmad; Rahardian, Fikri; Ismail, Galih Maulana; Jumadi, Jumadi; Desyani, Teti; Nirmala, Endar (Program Studi Teknik Informatika Universitas Pamulang, 2021)
The archive is created as evidence of the implementation of administrative activities of agencies / organizations. Most of the agencies/organizations do not anticipate to save their active archives. This will result in a build-up of archives. Lack of understanding of records management guidelines in an agency / organization so that the implementation is not in accordance with applicable regulations and resulted in the archive is considered inconsideient. The problems faced by programmers if they do not make a plan in advance will cause a lot of problems. The design method to be used is Unified Modeling Language or UML. By using the UML method, we can find out the next stages that will be done in the form of diagrams. If the E-Archive application has been created, it is very useful to facilitate the storage of archive data that previously still uses manuals such as Microsoft excel. The data will then be stored in the database so that it can easily update the archive data and can view the archive data as a whole.